Readiness for implementing a case management based long-term care program for older people - I Gede Putu Darma Suyasa (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Indonesia faces a rapidly ageing population, with Bali designated as a pilot province for implementing the Case Management Program for Long-Term Care (CMP-LTC). Assessing readiness among nurses and community cadres is crucial to ensure program success and sustainability. Purpose: To explored the readiness of nurses and community cadres to implement the CMP-LTC program for older people in Bali, Indonesia. Method: A descriptive qualitative design was applied using focus group discussions involving two nurses and eight community cadres selected purposively. Data were analyzed thematically based on Braun and Clarke’s approach while ensuring credibility through triangulation and member checking. Results: Six major themes emerged: (1) enhanced knowledge and skills after training, (2) the need for continuous and advanced learning, (3) limited resources and unclear legal authority, (4) sociocultural and community challenges, (5) teamwork and collaboration, and (6) increased empathy and motivation. Conclusion: Readiness for CMP-LTC implementation is multidimensional, encompassing personal competence, structural support, and sociocultural acceptance. Strengthening continuous education, resource provision, legal clarity, and intersectoral collaboration will enhance the effectiveness and sustainability of Indonesia’s long-term care services for older people.